Developing a Generic Methodology for Traffic Impact Assessment of a Mixed Land Use in Dhaka City (Journal of Bangladesh Institute of Planners, 2012)
A proficient transportation system has a great importance on the infrastructural as well as the overall economic development of a country. But the traffic volume of Bangladesh especially of the capital city Dhaka is growing at an alarming rate with the large number of population and development projects. The result is ultimately an inefficient transport system with traffic jam, congestion, irregular parking, low level of service, injured road network etc. A traffic impact assessment or TIA is an evaluation of the potential effects that a particular development’s traffic will have on the transportation network in its impact area. TIA includes formulation of traffic management schemes and recommendation of infrastructure for possible transportation and traffic problems that will be encountered during the construction and operation phases of projects. This article primarily focuses on developing a framework of TIA methodology for a mixed land use in context of Bangladesh. This study will use the TIA process to evaluate the effects of an ongoing project on its adjacent roads’ transportation system. From the ultimate result it is seen that, before the project was completed, the level of service of the New Market-Science Laboratory section of Mirpur road was E at base year condition (2009), but after the completion of the project the level of service of the same road has been turned into F at 2013.Journal of Bangladesh Institute of Planners Vol. 5, Dec 2012, pp. 119-128